Dark angel [compact disc, unabridged] - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Letty Davenport novel., 2023)
When a group of hackers threatens to take over the power grid of Minneapolis, putting thousands of lives at risk, the Department of Homeland Security and the NSA team up to prevent the attack. They need to find out who these dangerous hackers are ... and they need to do it quickly. Letty Davenport, the twentysomething daughter of Lucas Davenport, is brought on board to go undercover and infiltrate the group. Posing as a rogue programmer for hire, she and her reluctant partner from the NSA, Rod Baxter, head to Los Angeles to find the illusive group before it is too late.